Co-operation of the Latvia University of Agriculture with Schools - Aizsila, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article summarises experience of co-operation within three years (2010-2012) of the Institute of Education and Home Economics (IEHE) of Latvia University of Agriculture (LLU), Zemgale Region Competence Center and schools of Zemgale in consulting of research work of pupils. A topical problem – research work of pupils in the process of studies – has been investigated. The lecturers of the LLU support the teachers of schools in advising the learners’ research work. The aim of the article is conscious and substantiated necessity for co-operation of the university and schools in development of research papers of pupils. In the article 439 research papers of learners are theoretically and empirically analysed, summarized and evaluated. The influence of society on the development of the learners’ research skills has been clarified. The research work competition winners get LLU certificates that allow for entering the faculties of the university without competition after finishing school. Receiving of the certificate is a stimulus for further research.